PERANCANGAN ULANG TATA LETAK FASILITAS RITEL SETYA JAYA MATERIAL DI KABUPATEN BOGOR - Anggraini Putri Setyowati; Noviana Trianti; Belinda Desti Syahani; Husnul Arrafi; Khoirul Aziz Husyairi; Tina Nur Ainun (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The layout is one of the important factors that determine how well a business operates in the long run. A good layout can create an enjoyable shopping experience for customers. The focus of this study is on redesigning the facility layout in the retail business of Setya Jaya Material to make it more efficient. The analysis methods used are ARC and TCR. The initial condition of the facility layout at Setya Jaya Material retail shows an inefficient arrangement where there are inbound or outbound facilities on the left corner side that complicates the mobilization of goods and customers. The result of rearranging the facility layout is a relocation between the cashier and inbound or outbound because of their high proximity. The goal of relocating the cashier with inbound or outbound is to facilitate the mobilization of goods and customers, thus becoming more efficient.